Investment Choices and Returns: Insights on Indian Student Investors - Daksh Chouhan (Journal of Education in Specific Purpose, 2025)
This research paper explores the investment behaviors, choices, and returns of individual students, by creating a balance between present financial needs and future wealth creation. With growing awareness about financial planning, students are increasingly engaging in investment activities. The paper talks how various investment options available and types of investments preferred by various groups. Further it analyses the investments preferences and choices by segregating students based on various demographic factors. Drawing from both global and Indian contexts, the paper analyses how economic conditions, emerging technologies, and post-pandemic uncertainties have shaped investment preferences. The study seeks to understand how individual investors-particularly students-manage short-term expenses while aiming for long-term financial returns, offering insights into effective and sustainable investment strategies. It also explores how different financial theories effect student mindset and influence decision making.  Ultimately, this study contributes to a deeper understanding of how student investors can make informed decisions to optimize their returns while balancing present consumption and future financial goals.